A Successful Outcome of Twin Pregnancy in Patient with Systemic Lupus Erythematosus - A Case Report (Bangladesh Medical Journal, 2009)
A 28 years old lady was admitted in BSMMU with 4th gravida 33 wks. twin pregnancy with preeclampsia and anasarca. She is a known case of SLE for 4 years and was diagnosed at her 3rd pregnancy. At that time her antids DNA titre was 1100IU/ml. She was in prednisolone and aspirin. She was in remission phase and with advice of physician she got pregnancy. She was diagnosed as a case of twin pregnancy at 12 weeks of pregnancy.   DOI: 10.3329/bmj.v38i1.3585 Bangladesh Medical Journal 38(1) 2009 35-36